Present‐Day Mars' Seismicity Predicted From 3‐D Thermal Evolution Models of Interior Dynamics. Issue 6 (30th March 2018) - Plesa, A.‐C.; Knapmeyer, M.; Golombek, M. P.; Breuer, D.; Grott, M.; Kawamura, T.; Lognonné, P.; Tosi, N.; Weber, R. C.
Abstract: The Interior Exploration using Seismic Investigations, Geodesy and Heat Transport mission, to be launched in 2018, will perform a comprehensive geophysical investigation of Mars in situ. The Seismic Experiment for Interior Structure package aims to detect global and regional seismic events and in turn offer constraints on core size, crustal thickness, and core, mantle, and crustal composition. In this study, we estimate the present‐day amount and distribution of seismicity using 3‐D numerical thermal evolution models of Mars, taking into account contributions from convective stresses as well as from stresses associated with cooling and planetary contraction. Defining the seismogenic lithosphere by an isotherm and assuming two end‐member cases of 573 K and the 1073 K, we determine the seismogenic lithosphere thickness. Assuming a seismic efficiency between 0.025 and 1, this thickness is used to estimate the total annual seismic moment budget, and our models show values between 5.7 × 10 16 and 3.9 × 10 19 Nm. Key Points: We compute the cumulative seismic moment due to convective and cooling stresses from 3‐D thermal evolution models of Mars The annual seismic moment budget calculated from our models is between 5.7 × 10 16 and 3.9 × 10 19 Nm A new, self‐consistent model for the spatial distribution of seismicity is derived from 3‐D thermal evolution models